Terbinafine HCl Film-Forming Spray for the Treatment of Topical Fungal Infections - Soujith, Nidamanuri Bala Sai; Jawahar, Natarajan (Indian Journal of Pharmaceutical Education and Research, 2023)
Terbinafine HCl is an allylamine used to treat fungal infections. It has substantial side effects that can be mitigated by using a topical semisolid dose form. The objective of this study was to develop a 1% Terbinafine HCl film-forming spray formulation to treat topical fungal infections. The formulation was developed by combining polymers, penetration enhancer, plasticizer, and a suitable solvent system. The central composite design with 3 independent variables and 2 dependent variables is implemented to optimize the formulation. The film-forming spray was put through its tests to assess formulation and container-related parameters such as pH, spray angle, spray pattern, density, volume delivered for one actuation and evaporation time. From the study, it was observed that the concentration of ethyl cellulose and Eudragit RSPO has a greater influence on the viscosity of the spray solution, whereas the eutectic mixture has a greater influence on the drug permeation followed by the polymers. It also tested with various fungi, and it was found that formulation showed better fungicidal activity than the marketed product achieved by triple action. The stability studies have shown that the optimized formulation was stable with temperature of 25 ± 2°C and RH 60 ± 5(six months) on the pH, viscosity and visual appearance of the formulation. The study has concluded that the formulated film-forming spray formulation is highly efficient in treating topical and transdermal fungal infections when compared to the traditional dosage forms.
Keywords: Terbinafine HCl; Formulation; Fungal infection; Solid dosage forms; Ethyl cellulose